Taxonomy of prokaryotic viruses: 2018-2019 update from the ICTV Bacterial and Archaeal Viruses Subcommittee - Adriaenssens, Evelien M.; Sullivan, Matthew B.; Knezevic, Petar; van Zyl, Leonardo J.; Sarkar, B. L.; Dutilh, Bas E.; Alfenas-Zerbini, Poliane; Łobocka, Małgorzata; Tong, Yigang; Brister, James Rodney; Moreno Switt, Andrea I.; Klumpp, Jochen; et al. (Archives of virology, 2020)
This article is a summary of the activities of the ICTV’s Bacterial and Archaeal Viruses Subcommittee for the years 2018 and 2019. Highlights include the creation of a new order, 10 families, 22 subfamilies, 424 genera and 964 species. Some of our concerns about the ICTV’s ability to adjust to and incorporate new DNA- and protein-based taxonomic tools are discussed.